Physicochemical and Organoleptic Properties of Local Food-based Enteral Nutrition Product to Mitigate Patient Malnutrition - Lestari, Lily A.; Susetyowati; Setyopranoto, Ismail; Probosuseno; Astuti, Herni (Current Nutrition & Food Science, 2021)
Background: In Indonesia, to attain cost-effectiveness, home enteral formulas are produced from fresh foods, but they are not ready-to-use products, not durable, and have unstandardized nutrition contents. Objectives: We aimed to evaluate sensory characteristics and the physicochemical properties of a local food-based enteral nutrition product. Methods: We evaluated sensory characteristics of a local food-based enteral nutrition product consisting of color, odor, flavor, and texture using triangle test. The sensory evaluation involved 30 semi-trained sensory panelists. Physicochemical properties were also assessed through standardized laboratory analyses. The ingredients were arrowroot starch, rice flour, palm sugar, cork fish (Channa striata), tempeh powder, milk, and yellow pumpkins. The flavors were original, ginger and cinnamon. Panelists were asked to assess the color, odor, flavor and texture, and provide a score for each variable according to a 5-point Likert scale from strongly do not like to strongly like. The physicochemical properties, i.e. , the water and ash contents, water activity, antioxidant activity, heavy metal content, and viscosity, were analyzed. Results and Discussion: There were only significant mean rank differences of color between samples, while odor, flavor, and texture were not. Most panelists selected light brown, which was the original flavor, as their preferred color compared to ginger and cinnamon flavor (52.45 vs. 43.50 vs. 36.05, p=0.026). The most favorable odor was from the ginger flavor, but for flavor, almost all panelists selected the original flavor as being the best. The texture of all products was slightly sandy. The water, ash, Pb contents, Aw and antioxidant activity were 3.14%, 4.18%, 0.016 mg/kg, 0.22, and 14.1 ppm, respectively. Conclusion: The original product exhibited better organoleptic properties in terms of color and flavor, while the ginger flavor exhibited a better odor than the other variants. The physicochemical properties of the product met the Indonesian National Standard requirements.
Keywords: malnutrition